The Value of Early-Career Skills - Christina Langer; Simon Wiederhold (Center for Economic Studies and ifo Institute (CESifo), 2023)
We develop novel measures of early-career skills that are more detailed, comprehensive, and labor-market-relevant than existing skill proxies. We exploit that skill requirements of apprenticeships in Germany are codified in state-approved, nationally standardized apprenticeship plans. These plans provide more than 13,000 different skills and the exact duration of learning each skill. Following workers over their careers in administrative data, we find that cognitive, social, and digital skills acquired during apprenticeship are highly – yet differently – rewarded. We also document rising returns to digital and social skills since the 1990s, with a more moderate increase in returns to cognitive skills.
Keywords: I21; I26; J24; 330; returns to skills; apprenticeship plans; labor market; earnings; early-career skills